Public-Private Partnership In Indonesian Urban Water Sanitation And Hygiene Program: Human Resource Capacity’s Innovation - Nida Hanin Dary; Ismi Dwi Astuti Nurhaeni; Didik G. Suharto (Indonesian Association for Public Administration (IAPA), 2019)
Public-Private Partnerships (PPPs) in Indonesia still face constraints on the limited capacity of human resources. Indonesian PPP with the United States Agency for International Development (USAID) in the implementation of the Indonesian Water, Sanitation and Hygiene (IUWASH) program tries to improve Indonesian sanitation which in the lowest rank in ASEAN. However, the implementation is still facing problems because human resources in local governments in Indonesia have not been able to increase their capacity so that program assistance to the government has not been able to run optimally. Therefore, human resources in Indonesia are required to be improved to be internationally competitive and innovatively synchronized with the developing technology so that human resources in Indonesia can support sustainable development. This research seeks to provide innovation in the human resource management capacity to improve the performance of local government resources on PPP in IUWASH programs in Indonesia in the face of the 4.0 Industrial Revolution. This research was conducted with literature review methods. Efforts to increase human resource capacity are carried out by creating human resource strategic planning based on analysis of the situation and potential of human resources with international standardization in training and development.